Academic Development for University Students in light of High Performance Indicators (Case Study of Jazan University) - Al-Tell, Wae'l; Sywelem, Mohammed (Jordan Journal of Educational Sciences, 2017)
The purpose of this study was to determine the academic development practices among university students in light of high performance indicators selected from the literature of contemporary higher education, and to identify the perceptions of Jazan University students regarding these practices. The researchers designed a questionnaire of (21) items to collect the data from a random sample of (691) students. Results of the study revealed that the level of university students response regarding the academic development practices was moderate (mean=3.14), the mean scores of all responses ranged from 2.70 to 3.53. Results also showed that there were statistically significant differences among students’ responses due to college and GPA variables. However; results didn’t reveal any significant differences due to gender variable